Exploring Undergraduate Pharmacy Students Perspectives Towards Antibiotics Use, Antibiotic Resistance, and Antibiotic Stewardship Programs Along With the Pharmacy Teachers’ Perspectives: A Mixed-Methods Study From Pakistan - Khan, Faiz Ullah; Khan, Amjad; Shah, Shahid; Hayat, Khezar; Usman, Abubakar; Khan, Farman Ullah; Khan, Zakir; Karataş, Yusuf; Ahmad, Tawseef; Chang, Jie; Malik, Usman Rashid; Khan, Asad; et al. (Frontiers in Pharmacology, 2021)
Background: Antibiotic resistance (ABR) is one of the major issues around the globe. Timely education and awareness of pharmacy students regarding the appropriate use of antibiotics, ABR, and antimicrobial stewardships are required. Methods: The present study was first conducted in 12 (public and private sector) universities among undergraduate pharmacy students (UGPS) (n = 414) irrespective of their study year through a validated questionnaire, and the insights of pharmacy teachers were taken through in-depth semi-structured interviews in the second phase. For the quantitative data, different statistical methods were used, and data were presented in tabulated form, whereas inductive thematic interpretation was used to categorize themes and derive conclusions from qualitative evidence. Results: The majority of the students were males (n = 223, 54%) with the mean age group 19–23 years, and 20 faculty members were interviewed with a mean duration of 15 min. Students have good knowledge about antibiotics use and the majority purchased antibiotics through prescription (n = 277, 66.9%) during the last month and strongly agreed to stop unnecessary household storage (n = 183 44.2%). Most of the students have heard the terminologies related to antimicrobial resistance through social media while unaware (n = 104, 25.1%) of a Pakistan national action plan against AMR (antimicrobial resistance). Overall, respondents have a somewhat good understanding of the ABR. Regular use of antibiotics without consultation of a physician can lead to ABR and some wrong answers were observed (162, 39.1%; p > 0.05). The majority of the students (n = 198, 47.8%) and teachers believe that the current pharmacy syllabus must be swiftly updated with the new subjects related to ABR and AMS (antimicrobial stewardship) in Pakistan. The UGPS have emphasized (n = 220, 53.1%; Median = 1, IQR = 2) establishing a link between academia and hospitals. The ABR issue has been highlighted by pharmacy faculty members, who have urged students to take practical efforts toward ABR and AMS knowledge. Conclusion: The UGPS knowledge related to ABR and AMS must be updated. Students at the undergraduate level must get training in order to encourage the sensible use of antibiotics. Courses on ABR and AMS should be included in present pharmacy curricula.